Behavioral changes developed in children undergoing pediatric surgeries (Research, Society and Development, 2024)
The preoperative period is a time of hospitalization where feelings of fear and anxiety are common, especially among pediatric patients. During this time, nursing plays a crucial role in providing humanized care. Objective: To identify the profile of children undergoing pediatric surgical procedures and to determine the presence of behavioral and physiological changes in these children. This is an exploratory descriptive study with a quantitative approach, conducted through semi-structured interviews at a university hospital in the municipality of Rio de Janeiro, with a total of 89 participants. The research was approved by the Ethics Committee, under Opinion No. 2.940.781. The surgical profile of children undergoing surgery is typically over one year old, with a predominance of males. The most common surgeries included palatoplasty (12.36%), inguinal hernia (10.11%), orchidopexy (8.99%), and postectomy (6.74%). Most children did not show behavioral changes (78.65%) or physiological manifestations of fear (84.27%). The analysis of the pediatric patients’ profiles showed a correlation between the predominant gender and the types of surgical procedures performed. Furthermore, it was observed that age and cognitive development of children directly influence their behavioral changes and physiological manifestations of fear. The presence of a companion, the use of playful strategies, and effective communication are crucial in reducing preoperative fear and anxiety.